Infecção pelo vírus da hepatite B em catadores de materiais recicláveis em Goiânia-Goiás - Marinho, Tamíris Augusto (2013)
Hepatitis B virus (HBV) remains a major cause of liver disease worldwide despite vaccination programs implemented over the last decade. Worldwide, it is estimated that 2 billion people are infected with HBV and that more than 240 million are chronically infected. Patients with chronic hepatitis B are at risk for developing liver cirrhosis and hepatocellular carcinoma. Recyclable waste collectors have a lifestyle that is characterized by unfavorable social and environmental factors. There is currently very little data on HBV infection in this population. Therefore, the aim of the present study was to investigate the epidemiological profile of HBV infection in a population of recyclable waste collectors in Goiânia-GO. A cross-sectional survey was carried out with 431 individuals who were recruited in all 15 recycling cooperatives in Goiânia-GO. All individuals were interviewed, and their serum samples were tested for the presence of HBV serological markers. HBsAg and anti-HBc-positive samples were tested for HBV-DNA by polymerase chain reaction, and were genotyped by sequencing of the S region. The overall HBV prevalence infection was 12.8% (95% CI: 9.8-16.2). A multivariate analysis of risk factors showed that age >40 years and illicit drug use were independently associated with HBV infection. HBV-DNA was detected in 2/3 HBsAg-positive samples, and in 1/52 anti-HBc-reactive samples, resulting in an occult HBV infection rate of 1.9%. HBV genotypes A (subgenotype A1), D (subgenotype D3) and F (subgenotype F2) were identified. Only 12.3% of this population showed serological evidence of previous hepatitis B vaccination. These findings highlight the need of public health programs to recyclable waste collectors, including the hepatitis B vaccination.